Unveiling Digital Religious Phenomenology: the Negotiation of Literacy, Ethics, and Islamic Character Building among University Students - Jimi Harianto; Vetty Febriana; Roliyah; Widiyati (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
The pervasive integration of social media into university students' daily lives has created a complex digital-religious landscape, necessitating a deeper understanding of how Islamic values are negotiated online. This is particularly critical in Islamic teacher education, where future educators must embody and teach these values. This study aimed to investigate the phenomenological experience of Muslim student-teachers as they negotiate digital literacy, ethical practices (adab), and the construction of Islamic character within their social media ecosystems. A qualitative study employing Interpretative Phenomenological Analysis (IPA) was conducted. Data were collected through digital ethnography (observation of 9 WhatsApp/Telegram groups), in-depth phenomenological interviews with 24 students from teacher education programs (PGSD, PGPAUD, Penjaskesrek), and analysis of digital artifacts over 4 months. Three central themes emerged: (1) the contextual compartmentalization of adab, where students applied distinct ethical norms across different digital spaces; (2) strategic value negotiation, employing methods such as silence, private confirmation, or polite confrontation to resolve ethical dilemmas; and (3) a performative-internalization dialectic, where curated displays of piety on public platforms contrasted with more instrumental communication in private groups. Social media functions as a significant pedagogical space for the moral development of Muslim student-teachers, characterized by active negotiation rather than passive reception of norms. The findings underscore the necessity for educational strategies in Islamic higher education that foster critical digital religious literacy, moving beyond normative instruction to support reflective ethical reasoning in digital contexts.